2017
DOI: 10.3390/ani7110080
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Prevalence of Indigestible Foreign Objects in the Gastrointestinal Tract of Slaughtered Cattle and Body Condition Score

Abstract: Simple SummaryThe South African national cattle herd has increased from 6 million head since the 1970s to 14 million and more than two-thirds of the 14 million cattle in South Africa reside in the Eastern Cape Province (ECP), yet the Province has one of the highest poverty indexes. While this improvement is commendable, there are still many challenges to efficient livestock production notably infectious and non-infectious diseases. Many non-infectious diseases of the fore-stomach, such as rumenitis, rumen para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…In the current study, the highest record of indigestible foreign bodies was plastics (43.98%) in different stomach compartments of animals. This finding was in line with several findings from another nearby region of Ethiopia (Abebe & Nuru, 2011; Roman & Hiwot, 2010; Tesfaye, Yismaw, & Demissie, 2012), Nigeria (Nongcula et al., 2017; Remi‐Adewunmi et al., 2004). This may be due to less biodegradability of the synthetic plastic materials, negligent disposal and less availability of industry for recycling in the study areas.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the current study, the highest record of indigestible foreign bodies was plastics (43.98%) in different stomach compartments of animals. This finding was in line with several findings from another nearby region of Ethiopia (Abebe & Nuru, 2011; Roman & Hiwot, 2010; Tesfaye, Yismaw, & Demissie, 2012), Nigeria (Nongcula et al., 2017; Remi‐Adewunmi et al., 2004). This may be due to less biodegradability of the synthetic plastic materials, negligent disposal and less availability of industry for recycling in the study areas.…”
Section: Discussionsupporting
confidence: 90%
“…(118/384). This finding was higher than the studies reported by Tes- (Abebe & Nuru, 2011;Roman & Hiwot, 2010;Tesfaye, Yismaw, & Demissie, 2012), Nigeria (Nongcula et al, 2017;Remi-Adewunmi et al, 2004). This may be due to less biodegradability of the synthetic plastic materials, negligent disposal and less availability of industry for recycling in the study areas.…”
Section: Discussioncontrasting
confidence: 63%
“…To scale up silage production from FW, a mechanized and effective means of removing plastic packaging would be required, as plastic would interfere with the ensiling process and be detrimental to livestock health. Large pieces of plastic in the feed may lead to blockage of the gastrointestinal tract, internal injuries, and potentially livestock death [24]. In contrast, microplastics may bioaccumulate and negatively impact livestock health, growth, or reproduction as well as being potentially transferred to humans consuming the animal products [25].…”
Section: Fw Characteristicsmentioning
confidence: 99%
“…The significant increase in body temperature in affected buffaloes was linked to bacterial endotoxin and cytokine release due to bacterial infection (Aref and Abdel-Hakiem, 2013). In the affected buffalo, the substantial increase in respiratory and heart rates appeared due to the effect of elevated blood temperatures on the respiratory center and blood pressure (Omid and Mozaffari, 2014;Nongcula et al, 2017).…”
Section: Disucssionmentioning
confidence: 99%